To – a Polish operator of the theme-rheme structure. In search of generalization of its function and meaning - Danielewiczowa, Magdalena (Papers in Linguistics, 2024)
This article, representing structural semantics, is devoted to the meaning of the Polish “to” – an operator of the theme-rheme structure, which has a wide range of applications. It can be used in various types of sentences: constative, interrogative, imperative, and exclamatory, as well as in different positions of the same syntactic structure. According to the author, distinguishing several units of the “to” form has no theoretical or empirical basis. This operator organizes the informational structure in all utterances in which it appears, indicating its fundamental aspect: a necessary division between thematic and rhematic components. The division can be signaled in a purely prosodic manner (thanks to employing anti-cadence), yet it can also be strengthened and, additionally, commented upon lexically with the “to” operator. It is a speaker’s metatextual comment concerning the current speech act. All Polish “to” applications may be generalized with the gloss ‘not about somebody/something different than _ [you know what I am talking about], not something different than _’, which reveals this operator’s egocentric, metatextual, and indexical nature.